Supply chains in global production - Anatolii Mazaraki; Ganna Duginets (Економіка, Eкологія, Cоціум, 2017)
Introduction. Analyzing the current processes of global sales and sales interaction over the past two decades shows that the world’s system of exchanges has undergone significant changes that have been caused by a multitude of factors. The formation of a complex model of global production, determined by the peculiarities of the transformation of individual economies’ growth models, the specifics of their industrialization and the forms of development of their national production business, its institutional and market-wise restructuring and the degree of inclusion in the system of international division of labor. The change in the level and depth of the specialization of individual countries in the field of production and sale of products, in turn, has accelerated the overcoming of economic distance (which is measured by the cost of transport and information services). Based on the above, namely, within the framework of forming a new model of global production, the issue of studying the role and value of supply chains in this model is made relevant.